Foodie – Homemade food ordering application for food business - Wei Chuan, Cheah; Eh Phon, Danakorn Nincarean (2021)
The COVID-19 outbreak had seen the beginning in Malaysia of several new home kitchens and handmade food ordering systems. As the lockdown led to massive job losses and one of the greatest hits was the restaurant industry, some shifted to online catering and food delivery to feed a growing population for home-delivered food in the middle of the lockdown. The project aims to design and develop a homemade food ordering application for a homemade food business that can help the new entrepreneur to solve the following problem occurred likes the lack of resources to develop a food order application, time-consuming for the consumer to order homemade food by ordering face to face, and food safety and health concerns become higher in the pandemic outbreak.